Adult Education Enters the Cultural Competency Craze - Michael L. Rowland (Adult Education Research Conference, 2006)
This paper will provide a brief overview of the literature on cultural competency as it relates to health care. Cultural competency is a strategy to reduce and eliminate inequities in health care that are related to race, ethnicity, socioeconomic status, gender, and sexual orientation. The paper will provide a framework for health profession educators to understand cultural competency through the lens of adult education.
Keywords: Cultural Competency; Adult Education; Health Care Disparities